2014
DOI: 10.1039/c4dt01211a
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and photocatalysis of two novel 3D Anderson-type polyoxometalate-based metal–organic frameworks constructed from isomeric bis(pyridylformyl)piperazine ligands

Abstract: Two novel Anderson-type polyoxometalates (POMs)-based metal-organic frameworks (MOFs), namely, H{Cu2(μ2-OH)2L(1)[CrMo6(OH)6O18]}·4H2O (), {Cu2L(2)[CrMo(VI)5Mo(V)(OH)6O18](H2O)4}·4H2O () (L(1) = N,N'-bis(3-pyridinecarboxamide)-piperazine, L(2) = N,N'-bis(4-pyridinecarboxamide)-piperazine), are hydrothermally synthesized and structurally characterized by single-crystal X-ray diffraction, IR spectra, powder X-ray diffraction (PXRD) and thermogravimetric analyses (TGA). In complex , the hexadentate [CrMo6(OH)6O18]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…[24] It was reported that POMs are not only strong photo-oxidizing compounds but also strong Brønsted acid, so the biomass can be oxidized by POMs in solution under solar irradiation. [25] A variety of supported POMs, such as POMs/TiO 2 [26], POMs/MOFs [27], carbon quantum dots/silver nanoparticles/POMs [28], and POMs/organosilca frameworks [29], have been prepared for photocatalytic reactions. It would be very interesting to incorporate POMs onto the emerging 2D-structured, metal-free, visible light photocatalyst of g-C 3 N 4 , however, no such materials have been synthesized and tested for photodegradation of phenolics and dyes.…”
Section: Introductionmentioning
confidence: 99%
“…[24] It was reported that POMs are not only strong photo-oxidizing compounds but also strong Brønsted acid, so the biomass can be oxidized by POMs in solution under solar irradiation. [25] A variety of supported POMs, such as POMs/TiO 2 [26], POMs/MOFs [27], carbon quantum dots/silver nanoparticles/POMs [28], and POMs/organosilca frameworks [29], have been prepared for photocatalytic reactions. It would be very interesting to incorporate POMs onto the emerging 2D-structured, metal-free, visible light photocatalyst of g-C 3 N 4 , however, no such materials have been synthesized and tested for photodegradation of phenolics and dyes.…”
Section: Introductionmentioning
confidence: 99%
“…Functionalized piperazines [5], especially benzoylated derivatives, are our interest. In the past, mono or bisacylated piperazines with benzamide [6], nicotinamide [7] and isonicotinamide [811] residue were explored in terms of their NMR and complexation behavior. However, unsymmetrically substituted piperazines are rarely investigated [1213].…”
Section: Introductionmentioning
confidence: 99%
“…[42] As shown in Figure 10a, in the fluorescence spectra of the solution containing the catalytic STA-12(Fe, Mn)/sunlight/H 2 O 2 system and NaTA, peak intensity increases sharply to 930 within 10 min, [(AgL)(CF 3 SO 3 )]n -NS/7980 90 [23] H[Cu 2 (μ 2 -OH) 2 L 1 (CrMo 6 (OH) 6 O 18 )]·4H 2 O -SS/780 87 [48] [Cu 2 L 2 (CrMo 6 (OH) 6 [49] UiO-66(1.25Ti) 10 and 1000 SS/80 82 [50] [(CH 3 ) 2 NH 2 ] . [42] As shown in Figure 10a, in the fluorescence spectra of the solution containing the catalytic STA-12(Fe, Mn)/sunlight/H 2 O 2 system and NaTA, peak intensity increases sharply to 930 within 10 min, [(AgL)(CF 3 SO 3 )]n -NS/7980 90 [23] H[Cu 2 (μ 2 -OH) 2 L 1 (CrMo 6 (OH) 6 O 18 )]·4H 2 O -SS/780 87 [48] [Cu 2 L 2 (CrMo 6 (OH) 6 [49] UiO-66(1.25Ti) 10 and 1000 SS/80 82 [50] [(CH 3 ) 2 NH 2 ] .…”
Section: Determination Of Hydroxyl Radicalmentioning
confidence: 99%
“…• , therefore it could be used as a selective probe in sensing • OH radicals. [42] As shown in Figure 10a, in the fluorescence spectra of the solution containing the catalytic STA-12(Fe, Mn)/sunlight/H 2 O 2 system and NaTA, peak intensity increases sharply to 930 within 10 min, [(AgL)(CF 3 SO 3 )]n -NS/7980 90 [23] H[Cu 2 (μ 2 -OH) 2 L 1 (CrMo 6 (OH) 6 O 18 )]·4H 2 O -SS/780 87 [48] [Cu 2 L 2 (CrMo 6 (OH) 6 [49] UiO-66(1.25Ti) 10 and 1000 SS/80 82 [50] [(CH 3 ) 2 NH 2 ] . [Cu 2 (CN) 3 ] 3.7 and 100 NS/1440 91 [24] STA-12(Fe, Mn) indicating that • OH radicals were truly produced in the system.…”
Section: Determination Of Hydroxyl Radicalmentioning
confidence: 99%